Capital Grants For Local Infrastructure Provision In Perspective Of Allocative Efficiency: Evidence From Indonesia - Naufal Azaki; Achmad Lutfi (Brawijaya University, 2023)
This paper points out reflection on theoretical and empirical literature on the implementation of capital grants or specific purpose transfers as the conceptual basis of Dana Alokasi Khusus (DAK) in Indonesia. As one of the types of intergovernmental transfers, DAK plays a significant role in the local infrastructure provision, particularly in basic services such as roads, housing, drinking water, sanitation, education, irrigation, and tourism. This study uses a literature review approach of (and with no limits on) 16 empirical research results. The paper aims to analyze how far capital grant (DAK) is implemented, the challenges and problems that arise, and the dynamics of policy from the perspective of Allocative Efficiency. The study notes some practical suggestions for improving the DAK design and agenda for future research needed, including the adoption of MTEF in DAK planning for local government, reshaping the formula & criteria used in DAK allocation, possibility of giving relaxation on reallocation authority to spending unit, developing evaluation indicators with a focus on the efficiency & effectiveness of DAK, and directing the influence of political actors & process to improve the quality of policy.